2023
DOI: 10.17582/journal.sja/2023/39/s1.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Palatability Level of Dried Rice as an Alternative Feed Ingredient to Subtitute Corn and Rice Bran

Rusli Tonda,
Lili Zalizar,
Wahyu Widodo
et al.

Abstract: | Indonesia is among the highest organic waste-generating countries, with an average of 12 × 106 t yr–1. After being processed, organic waste is highly potential to contribute to animal farming, and “aking rice” is one such product. After cleaning and rinsing, rice remains are sundried to reach a water content of < 14 %. However, no literature or findings are yet to discover whether “aking rice” is palatable for poultry. Therefore, this study is focused on determining “aking rice” palatability to see its ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…The ash content in dried rice ranges from 0.3% to 3%. These results are strengthened by the findings of previous studies [21,30,36,50]. Since the crude protein contents in the samples were detected alike-10.64%, 10.30%, and 10.64% in T1, T2, and T3, respectively-the difference can be assessed as insignificant.…”
Section: Quality Of Dried Rice As a Feed Ingredientsupporting
confidence: 54%
“…The ash content in dried rice ranges from 0.3% to 3%. These results are strengthened by the findings of previous studies [21,30,36,50]. Since the crude protein contents in the samples were detected alike-10.64%, 10.30%, and 10.64% in T1, T2, and T3, respectively-the difference can be assessed as insignificant.…”
Section: Quality Of Dried Rice As a Feed Ingredientsupporting
confidence: 54%
“…The application of dry rice under heat stress by sowing method at 10 a.m will suppress the stress level in chicken as shown by the immune level which is not decreased. The same statement conveyed by Tonda et al [24,25] that dry rice is good for broilers. Low calories in dry rice caused the body's calory production would not be excessive, thereby it would reduce the stress level in broiler, reduce painting, and avoid the wet dropping.…”
Section: Antibodymentioning
confidence: 53%
“…Dry rice has some advantages because it has low calories and contains high resistant starch [21]. The previous research as reported by Tonda et al [24] showed that dry rice has advantages such as high palatability. Dry rice not only has high palatability, but it can also be used as a substitute for corn and rice bran [25].…”
Section: Introductionmentioning
confidence: 99%
“…Data from analysis of the physical and chemical properties of modified flour were tabulated in Microsoft Excel and then carried out through ANOVA [12,13].…”
Section: Discussionmentioning
confidence: 99%